2020
DOI: 10.7150/ijbs.36955
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin induces colorectal carcinoma cells apoptosis and autophagy by targeting galectin-1/JNK signaling axis

Abstract: Colorectal carcinoma (CRC) is the third most common malignant tumor pathology worldwide. Despite progress in surgical procedures and therapy options, CRC is still a considerable cause of cancer-related mortality. In this study, we tested the antitumor effects of shikonin in CRC and tried to identify its potential mechanism. The potential target, molecular mechanism as well as in vitro and in vivo antitumor effects of shikonin in CRC cells were determined by an integrative protocol including quantitative proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 72 publications
0
24
0
1
Order By: Relevance
“… 33 However, Zhang has found that autophagy plays a stimulative role in the development of CRC. 34 Meanwhile, autophagy can occur in tumors with the opposite function: protective autophagy and lethal autophagy. In this study, SERPINA1 promotes autophagy, and then autophagy plays an anti-tumor effect in COAD.…”
Section: Discussionmentioning
confidence: 99%
“… 33 However, Zhang has found that autophagy plays a stimulative role in the development of CRC. 34 Meanwhile, autophagy can occur in tumors with the opposite function: protective autophagy and lethal autophagy. In this study, SERPINA1 promotes autophagy, and then autophagy plays an anti-tumor effect in COAD.…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin remains one of the most effective chemotherapy agents against various types of cancer in vitro and vivo 13 . Prior study has shown that Shikonin could inhibit the proinflammatory milieu generated at the early phase of colon cancer 14 , induce CRC cells apoptosis and autophagy through JNK signaling pathway 15 , and inhibit the metastatic progression in CRC via up-regulating the expression of SIRT2 16 . However, these studies were mainly limited to reveal molecular targets in traditional pathways, which were hard to interpret the pharmacological mechanisms thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies have found that autophagy and apoptosis play a collaborative role in the treatment of CRC, but the precise mechanism of their collaboration is unclear. According to the report, the activation of Galectin-1 induced by shikonin potently activates apoptosis in colorectal carcinoma cells and autophagic cell death both in vitro and in vivo [ 33 ]. The accumulation of ROS induced by shikonin promotes the formation of Galectin-1 dimerization, which induces autophagy and apoptosis of downstream cells by activating the JNK signaling pathway, eventually leading to cell death together.…”
Section: The Main Way Of Crosstalk Between Autophagy and Apoptosis Inmentioning
confidence: 99%
“…Kim K et al showed intracellular ROS production played a critical role during ECZ-induced apoptosis and autophagy of colon cancer cells and that increasing ROS generation by the inhibition of autophagy results in enhanced apoptosis [ 89 ]. Furthermore, studies have found that Shikonin trigger the dimerization of Galectin-1 by inducing the accumulation of ROS, which eventually lead to autophagy and apoptosis of colorectal cancer cells [ 33 ]. It is well known that ROS over-production can trigger ER stress.…”
Section: The Main Regulatory Factors Of the Interaction Between Autopmentioning
confidence: 99%